Embryo Implantation In Intracytoplasmic Sperm Injection-Stimulated Cycle Using Testicular And Epididymal And Ejaculated Sperm From Azoospermic, And Severely- Teratospermic Men. - Ridha-Barzanchi, Mundhir T.; Khunda, Sarmad S.; AI-Anssari, Saeeda, A. M.; Kanan, Zuhair A.; Khunda, Sarmad S.; AI-Omari, Wafa R. S.; Al-Badri, Abedal H. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: The infertility affects about 20% to 28% of Iraqi population and the primary and secondary infertility cover 80% and 20% of infertility cases respectively. It has beenshown that the major male infertility factors include oligospermia, astheno-spermia, teratospermia and azoospermia.Objectives: The objective of this study was to compare the fertilizing capacity, in vitro embryonic developmental rate and embryo implantation following the use of epididymal,testicular, and ejaculated sperm in azoospermic and severely teratospermic men. Patients and Methods: The males in experiment one were divided into three groups, severely teratospermic group (STSG, n=44), azoospermic-epididymal group (ASEG, n=35) and azoospermic-testicular group (ASTG, n=40). In experiment two the azoospermic patientswere divided into two groups, obstructive (OASG, n=35) and non-obstructive (NASG, n=42). Both groups were underwent testicular extraction and intracytoplasmic sperminjection (TESE-ICSI) treatments.Results: Concentration of FSH, LH, prolactin was significantly higher in non-obstructive group compared to obstructive group (P